2012
DOI: 10.1186/1471-2415-12-18
|View full text |Cite
|
Sign up to set email alerts
|

Subacute phase treatment of subperiosteal hematoma of the orbit with epidural hematoma in the frontal cranial fossa: Case report

Abstract: BackgroundSubperiosteal hematoma of the orbit is one of the rare lesions that cause exophthalmos after craniomaxillofacial trauma. Presently, there is no consensus for how to treat this disease. Although some reports have suggested a conservative type of therapy, others have recommended surgical treatments be done during the early stages.Case presentationThis case report provides details on the clinical course of a 9-year-old girl with subperiosteal hematoma of the orbit. In this particular patient, a rare cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The treatment of choice, however, remains controversial. Many studies recommend early surgical interventions for rapid recovery and to prevent sequelae [7]. In contrast, other reports recommend observation to prevent surgical complications such as local infections and re-bleeding [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of choice, however, remains controversial. Many studies recommend early surgical interventions for rapid recovery and to prevent sequelae [7]. In contrast, other reports recommend observation to prevent surgical complications such as local infections and re-bleeding [8].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other reports recommend observation to prevent surgical complications such as local infections and re-bleeding [8]. It is important to note that successful conservative treatment was reported in children older than ten years who were not in the critical period for vision development [1,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Subperiosteal hematoma is an infrequent condition, most commonly reported in the human medical literature in relation to the orbit. Development of hemorrhage in this region has been reported to result from trauma, infection/inflammation, or an underlying coagulopathy . The condition is considered to be spontaneous when there is no evidence of an underlying pathogenic mechanism .…”
Section: Discussionmentioning
confidence: 99%
“…The condition is considered to be spontaneous when there is no evidence of an underlying pathogenic mechanism . Less common are reports of subperiosteal hemorrhage affecting the central nervous system due to extradural compression . Only one report of spinal subperiosteal hemorrhage exists in the medical literature.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of optic nerve compression, surgical drainage should be performed to prevent permanent optic nerve damage. Mikami et al 9 reported that in subperiosteal orbital hematoma, immediate surgical intervention and drainage prevent further complications. 33 Decrease in visual acuity commonly occurs, but it is often not a result of compressive optic neuropathy, and frequently it resolves during the recuperative period.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%